2017
DOI: 10.1016/j.algal.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A fast and reliable strategy to generate TALEN-mediated gene knockouts in the diatom Phaeodactylum tricornutum

Abstract: Reverse genetics techniques are powerful tools for studying gene functions. In the model diatom Phaeodactylum tricornutum, RNAi-mediated knockdown of genes still is the most commonly used reverse genetics technique. Due to the diploidic life cycle missing reproduction in lab cultures, many commonly used techniques to create knockout instead of knockdown lines are not applicable in P. tricornutum. These limitations can be overcome by using genome editing approaches like TALEN (Transcription activator-like effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 65 publications
2
62
0
Order By: Relevance
“…Technical improvements should decrease the TALENs production costs and increase the feasibility of producing these endonucleases in a short time. A protocol by Sanjana et al (2012) for generating fast, easy, and affordable TALEN constructs, based on a library of monomers, each representing one repeat unit of a TALE, and a two-step Golden-gate reaction, has recently been adopted for diatoms generating knockout strains for blue light Aureochrome photoreceptors in P. tricornutum (Serif et al 2017). Moreover, compact TALENs (cTALENs) (Beurdeley et al 2013), a new TALEN scaffold where the FokI catalytic head has been replaced by the I-TevI homing endonuclease, have been designed for diatoms.…”
Section: Tale Nucleasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Technical improvements should decrease the TALENs production costs and increase the feasibility of producing these endonucleases in a short time. A protocol by Sanjana et al (2012) for generating fast, easy, and affordable TALEN constructs, based on a library of monomers, each representing one repeat unit of a TALE, and a two-step Golden-gate reaction, has recently been adopted for diatoms generating knockout strains for blue light Aureochrome photoreceptors in P. tricornutum (Serif et al 2017). Moreover, compact TALENs (cTALENs) (Beurdeley et al 2013), a new TALEN scaffold where the FokI catalytic head has been replaced by the I-TevI homing endonuclease, have been designed for diatoms.…”
Section: Tale Nucleasesmentioning
confidence: 99%
“…For temporary induction or inhibition of endonuclease expression, the nitrate reductase (NR) promoter has been used, as the expression of the NR gene can be induced or inhibited by exchanging ammonia by nitrate as a nitrogen source or vice versa. The NR promoter construct, originally developed for the diatom Cylindrotheca fusiformis (Poulsen and Kröger 2005), and then adapted for P. tricornutum and T. pseudonana (Poulsen et al 2006;Miyagawa et al 2009;Hempel et al 2011;Chu et al 2016;Lau et al 2016), has already been used to drive a strong expression of TALEN (Serif et al 2017) and Cas9 (Stukenberg et al 2018) in P. tricornutum cells grown in nitrate-containing media. However, studies of NR promotor-driven GFP expression in P. tricornutum also indicated that gene expression cannot be completely switched off in the absence of nitrate (Chu et al 2016).…”
Section: Expression Of Endonuclease Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome-enabled studies have revealed genes, regulatory elements and epigenetic factors potentially controlling the expression of diverse phenotypes. It is only recently, however, that genome editing tools such as CRISPR/Cas (Sander and Joung 2014;Doudna and Charpentier 2014;Lander 2016) and TALENs (Gaj, Gersbach, and Barbas 2013) have become available, including in diatoms (Daboussi et al 2014;Hopes et al 2016;Nymark et al 2016;Weyman et al 2015;Serif et al 2017), enabling us to improve our understanding of individual genetic factors for the evolution and biology of diatoms. The introduction of gene-targeting by high frequency HR allows precise genetic changes via knock-in of a particular sequence at a specific locus, rather than just gene knock-out.…”
Section: Introductionmentioning
confidence: 99%